The Reporting Quality of Randomized Controlled Trial Abstracts in Plastic Surgery. (29th July 2019) - Gallo, Lucas; Wakeham, Scott; Dunn, Emily; Avram, Ronen; Thoma, Achilleas; Voineskos, Sophocles
Abstract: Background: When evaluating randomized controlled trials (RCTs), clinicians will often refer to the abstract for an initial assessment of the results and to determine whether a full-text review is warranted. Objectives: This project aims to assess the reporting quality of RCT abstracts published within the top 5 plastic surgery journals utilizing the Consolidated Standards of Reporting Trials (CONSORT) for abstracts checklist. Methods: A computerized database search of OVID MEDLINE was performed. All primary RCTs published within the top 5 plastic surgery journals (by 2016 International Scientific Indexing impact factor) from 2011 to 2018 were included. Two reviewers, blinded to journal and author, independently and in duplicate, scored abstracts employing the 16-item CONSORT for abstracts checklist. Results: This review identified 126 RCTs that satisfied the inclusion criteria. Included studies were distributed across 5 journals: Plastic and Reconstructive Surgery (n = 83), JAMA Facial Plastic Surgery (n = 8), Aesthetic Surgery Journal (n = 33), Journal of Reconstructive Microsurgery (n = 2), and the Journal of Hand Surgery – European Volume (n = 0). Mean overall item adherence across all abstracts was 7 (SD ± 2). The most poorly reported items were "trial registration, " "method of randomization, " and "source of trial funding" and appeared in 4%, 2.4%, and 0% of abstracts, respectively. Conclusions: There is limited adherence to the CONSORT for abstracts checklist among RCT abstracts published within the top 5 plastic surgery journals. Given the reliance of clinicians on abstract reporting, omitting essential trial details can lead to an inaccurate interpretation of trial results and improper application in clinical practice. Active endorsement of the CONSORT for abstracts checklist is required to improve the quality of RCT abstract reporting.